A Financial Model for Economic Analysis of Cement Factory - Bidabad, Bijan; Sherafati, Mahshid; Mohammadi, Rohollah (International Journal of Business and Management Future, 2019)
In this paper, a method is presented to combine financial data and financial statements for economic analysis, which consequently introduces a software application for determining the economic structure of a cement factory. This software converts nearly 300 items of raw data of a cement factory to almost 4 times more economic-analytic information. The software analyzes the quantity and quality of production activities in addition to the cost structure of the concerned cement factory. It provides more than 80 descriptive figures, which have been defined previously and are applied to illustrate the economic structure of the cement factory. The calculated tables and figures are able to guide decision makers of the cement factory with regard to inefficiencies, obstacles, and various problems in the factory. In the end, a set of policies for increasing production efficiency and reducing costs are expressed briefly, which can be considered as the primary plans to operationalize the analytical information of the software. It is worth to mention that the presented structure of the software has been designed for Abyek Cement Factory. However, it can be employed as a guiding project for other cement factories as well. In other words, the software can be rebuilt with consideration of their specific information by revising and adjusting the software structure to cover their specific features.